Magnitude and factors associated with anemia among pregnant women attending antenatal care in public health centers in central zone of Tigray region, northern Ethiopia: a cross sectional study - Teklit Grum; Ermyas Brhane; Solomon Hintsa; Gizienesh Kahsay (BMC, 2018)
Abstract Introduction Anemia is defined as a low blood hemoglobin concentration (< 11 mg/dl). It is a global public health problem especially in pregnant women and is associated with higher risk for both maternal and perinatal mortality and morbidity. In developing countries, like Ethiopia where anemia is common, determining the magnitude and identifying factors that are associated with anemia is necessary to control it. Methods Facility based cross sectional study design were conducted among 638 pregnant women attending antenatal care in public health centers in central zone of Tigray region, Northern Ethiopia from November 1/2017 to January 30/2018 using stratified multi stage sampling method. The data was collected through interviewing the pregnant women face to face after getting informed consent using structured and pre-tested questionnaire. The data was coded and entered in to Epi-info 7 then exported to Stata 14 for cleaning and further analysis. Both Bivariable and multi variable logistic regression model was used in the data analysis. Results The overall magnitude of anemia (hemoglobin level < 11 mg/dl) were found that 16.88% (95% CI: 13.95%, 19.8%). Factors which were significantly associated with anemia in the multivariable analysis were: history of malaria attack 1 year prior to study period (AOR = 4.73, 95% CI: 2.64, 8.46), women who had history of excessive menstrual bleeding (AOR = 3.94, 95% CI: 2.11, 7.35), unplanned pregnancy (AOR = 2.5, 95% CI: 1.4, 4.42) and three times or less meal frequency (AOR = 1.89, 95% CI: 1.02, 3.5). Conclusion The magnitude of anemia among pregnant were found that 16.88%. Malaria attack, excessive menstrual bleeding, pregnancy planning and meal frequency were found that significantly associated with anemia in the multivariable analysis. Pregnant women are recommended to increase meal frequency. Health providers should give attention to pregnant women who had history of malaria attack, excessive menstrual bleeding and women whose pregnancy were not planned.